THE EFFECT OF MARZANO’S MODEL ACCOMPANIED BY VISUAL PRESENTATION TOOLS ON DEVELOPING CERTAIN COGNITIVE ABILITIES AND THE SKILLS OF SPIKING AND BLOCKING IN VOLLEYBALL - Al-Zubaidi, Amer Rashid Shayyal (Journal Olahraga Rekat (Rekreasi Masyarakat), 2026)
Background. Technological advancement plays a significant role in providing educators and coaches with modern teaching tools, devices, and instructional aids, both on cognitive and practical levels, which facilitate the process of delivering information to learners. Objectives. The current study aimed to examine the effect of Marzano’s model, accompanied by visual presentation tools, on developing certain cognitive abilities as well as the volleyball skills of spiking and blocking. Method. The researcher employed an experimental methodology on a primary research sample consisting of 27 youth players from the Al-Hay Sports Club. The sample was divided into an experimental group and a control group. The experimental group was trained according to Marzano’s model, while the control group followed the conventional method used by the coach. After the completion of the experimental intervention, the results were collected and analyzed statistically. Results. The findings indicated an improvement in certain cognitive abilities as well as the spiking and blocking skills among both research groups. However, the experimental group demonstrated superiority across the studied variables, reflecting the effectiveness of the Marzano model in enhancing both mental and motor performance. Conclusion. Based on these results, it is recommended to implement Marzano’s model in all sports activities, particularly in volleyball, due to its tangible positive effects on players’ cognitive development and skill acquisition, as evidenced by the outcomes of this study.